CODI - co-criação de brinquedos através do uso de tecnologia - Usó, Vanessa Ghiraldeli (2018)
This study reports a social Project based on a user-centered design process named CODI Project: a collaborative process to co-create toys with children hospitalized at the Cancer Hospital, through the use of Virtual Reality (VR) and 3D Printing technologies. CODI Project aims to provide an experience different from that experienced daily by hospitalized children, seeking distraction and possible relief from their fear of needles, crediting the authors of the respective drawings and valuing the development process, regardless of the esthetic result of the pieces. The Project has two main phases: (1) the cocreative process with the children; (2) the production of prototypes based on the children’s creative drawings. For the activities with the children, static virtual reality environments were created, using VR in order to distract them from the hospital environment and the situation they are and also to influence themes for drawings requested for the children to perform, at the end of the activity, using color pencils and paper. Secondly, after the selection of the drawings, 3D modeling was done through digital sculpting and the project was executed by rapid prototyping, using additive and subtractive technologies, as well as a vacuum forming machine. In this study, the development of three projects are fully reported: the activity with the childrens and the selected drawings to be modeled and transformed into toys, making these children the respective designers of their own toys. It was concluded that, despite the technology required and considerably high cost for producing custom pieces with 3D printing, the project was fully executed successfully. It was perceived a possibility of project growth for various audiences turning ideas from paper to the 3D universe. In addition, this initiative shows the potentials for interdisciplinary approaches between Product Design and Health Sciences. The challenges and benefits of this collaborative interdisciplinary process are reported herein.